Team Games Tournament: Diarrhea Prevention Education for School Children through Team Play and Video Media - Yulanda, Fitria; Arif, Rifda Nur Achriyana; Aridamayanti, Bernadetta Germia; Herawati (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2025)
Diarrhea is one of the leading causes of morbidity and mortality among children in Indonesia. Health education in schools serves as a key strategy in reducing the incidence of diarrhea in children. This study aims to analyze the effectiveness of the Team Games Tournament (TGT) method combined with video media in improving elementary school students’ knowledge of diarrhea prevention. A quasi-experimental method with a pre-test–posttest design and a Non-Equivalent Control Group Design was employed, involving 70 respondents divided into intervention and control groups. The results showed a significant increase in diarrhea prevention knowledge scores in the intervention group compared to the control group (p<0.05). This indicates that game-based learning is more effective than conventional educational methods. Based on these findings, the TGT method can be considered an innovative and interactive educational strategy within school health programs and is recommended for broader implementation alongside evaluations of behavioral changes in diarrhea prevention.